2021
DOI: 10.1002/aelm.202101022
|View full text |Cite
|
Sign up to set email alerts
|

Polarization‐Induced Band‐Alignment Transition and Nonvolatile p‐n Junctions in 2D Van der Waals Heterostructures

Abstract: optoelectronic devices. The atom-scale thickness and the absence of surface dangling bonds enable them significant advantage for the electrostatic control and van der Waals (vdW) integration, which is essential for the realization of functional devices with scaling dimensions and ultralow off-state power consumption. [5,6] The formation of p-n junctions is a fundamental step for the realization of 2D semiconductor devices used in transistors, memories, photodetectors, solar cells, and light-emitting diodes. [7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 49 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…The OOP localization of the CBM and VBM states arises from the polarization-induced band bending. 38,52 For the case of R up = 18.75%, the bands of the P down and P up regions are not degenerate (Fig. 4b).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The OOP localization of the CBM and VBM states arises from the polarization-induced band bending. 38,52 For the case of R up = 18.75%, the bands of the P down and P up regions are not degenerate (Fig. 4b).…”
Section: Resultsmentioning
confidence: 94%
“…Our recent studies have revealed that the electronic structures and carrier density of α-In 2 Se 3 depend on the polarization orientation and phase structure. 38,39 Despite these advances, it remains challenging to understand the domain switching dynamics in α-In 2 Se 3 , including the domain nucleation and growth process, since the evolution of the FE domains usually takes place on very short timescales at the atomic scale. Moreover, a qualitative relationship between the electronic structures and domain textures of α-In 2 Se 3 ferroelectrics remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Cao et al 41 reported 2D WSeTe/XS 2 (X = Hf, Sn, and Zr) vdW heterojunctions, and constructed six different structural models for the WSeTe/HfS 2 bilayer, the WSeTe/SnS 2 bilayer, and the WSeTe/ZrS 2 bilayer, respectively. Yang et al 42 considered six stacking configurations of MoSe 2 /GaN interfaces to confirm the most stable heterojunction model, and obtained them through the translation method. Yu et al 43 considered multiple atomic coincidence patterns when constructing the Janus MoSSe/WX 2 (X = S and Se) vdW heterojunction models.…”
Section: Resultsmentioning
confidence: 99%
“…Usually, the situation is that one layer gets electrons and another layer loses electrons. Previous research studies 24–86 on 2D vdWs semiconductor heterostructures with type-II band alignment are listed in Table 1. Some of them have been proved theoretically to be Z-scheme photocatalysts for water-splitting.…”
Section: Introductionmentioning
confidence: 99%